Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1093/brain/124.11.2319
|View full text |Cite
|
Sign up to set email alerts
|

Does diabetes target ganglion neurones?: Progressive sensory neurone involvement in long-term experimental diabetes

Abstract: Targeting of dorsal root ganglia by diabetes could account for the selective sensory abnormalities that patients with early diabetic polyneuropathy develop. In this work, we addressed survival, phenotype and gene expression in sensory neurones in lumbar dorsal root ganglia in a long-term model of experimental streptozotocin-induced diabetes in rats, designed to reflect human disease. Motor and sensory conduction slowing developed early, by the 2-month time point. At 2 months, sensory neurones had no detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
111
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 62 publications
15
111
2
1
Order By: Relevance
“…Others detect some loss of DRG (Russell et al, 1999;Zochodne et al, 2001;Kishi et al, 2002) and in particular there is a statistically significant loss of large DRG neurons (Kishi et al, 2002). Using rigorous counting techniques, Zochodne et al, concluded that there was no significant loss of neurons in the DRG of diabetic animals (Zochodne et al, 2001); although this study did detect a 14.5% decrease in the mean number of neurons (determined by nuclei). There is clear evidence that not all neurons are affected equally and, as with human patients, not all rodents develop the same degree of neuropathy or the same degree of neuronal injury.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Others detect some loss of DRG (Russell et al, 1999;Zochodne et al, 2001;Kishi et al, 2002) and in particular there is a statistically significant loss of large DRG neurons (Kishi et al, 2002). Using rigorous counting techniques, Zochodne et al, concluded that there was no significant loss of neurons in the DRG of diabetic animals (Zochodne et al, 2001); although this study did detect a 14.5% decrease in the mean number of neurons (determined by nuclei). There is clear evidence that not all neurons are affected equally and, as with human patients, not all rodents develop the same degree of neuropathy or the same degree of neuronal injury.…”
Section: Discussionmentioning
confidence: 54%
“…Multiple studies report activation of caspases in DRG neurons both in vitro and in vivo (Russell et al, 1999;Srinivasan et al, 2000;Kishi et al, 2002;Russell et al, 2002;Cheng and Zochodne, 2003;Schmeichel et al, 2003;. Others detect some loss of DRG (Russell et al, 1999;Zochodne et al, 2001;Kishi et al, 2002) and in particular there is a statistically significant loss of large DRG neurons (Kishi et al, 2002). Using rigorous counting techniques, Zochodne et al, concluded that there was no significant loss of neurons in the DRG of diabetic animals (Zochodne et al, 2001); although this study did detect a 14.5% decrease in the mean number of neurons (determined by nuclei).…”
Section: Discussionmentioning
confidence: 57%
“…The neuronal cell bodies in the DRG possibly are more capable of responding to metabolic insult through constant synthesizing and refolding of proteins than the axonal compartment, which would explain why we did not observe abundant alterations in the DRG proteome/ metabolome. Perikaryal preservation is a key feature of DN because no neuronal loss was detected in the DRG after 12 months of hyperglycemia in STZ-diabetes (31,32). The DRG plays a crucial role in axonal support, as evidenced by findings in STZ-diabetes when direct support of DRG neurons through intrathecal administration of insulin (which did not reduce hyperglycemia) improved SN conduction velocity and protected against distal axonal atrophy and intraepidermal nerve fiber loss (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies indicate some loss of DRG neurons (1,36), and in particular there is a statistically significant loss of large DRG neurons (36). In one study (37), using rigorous counting techniques of DRG nuclei in 6 -12 pairs of sections from the whole DRG, it was concluded that there was no loss of neurons in the DRG from diabetic animals. In fact, this study showed a 14.5% decrease in the mean number of neurons (determined by nuclei) per ganglion in 12-month diabetic animals (31,629 Ϯ 2,427 neurons) compared with that of control animals (36,986 Ϯ 3,035).…”
Section: Discussionmentioning
confidence: 99%